Competitive ability of cultivated rice MR219 and MR269 against weedy rice biotypes - Olajumoke, Abdulrahman Bashira (2016)
An investigation to evaluate the competitive ability of MR219 and MR269 cultivated rice against three weedy rice biotypes viz: awn-spikelet (AWB), open panicle (OWB) and compact panicle (CWB) weedy rice biotypes was carried out in the greenhouse, Field 2, Faculty of Agriculture, Universiti Putra Malaysia from October, 2014 to November, 2015. The experiment was designed in a randomized complete block design with four replications. The replacement series method was used to vary the weedy rice density to cultivated rice at proportions of 00:100, 25:75, 50:50, 75:25 and 100:00 in other to evaluate the effect of density and their competitiveness. The result showed that the growth of the cultivated rice was affected differently by different biotypes of weedy rice. The density of weedy rice within the two cultivated rice was significant (p < 0.05) on the growth of MR219 and MR269. Increasing relative yield loss (RYL) of both cultivated rice was observed as weedy rice density increases. While this increase was significant (p < 0.05) for the effect of CWB and OWB on the RYL of the MR219, only AWB significantly reduced the RYL of MR269. Under varying nitrogen (N), MR269 produced higher yield grain in monoculture and compared to MR219. The application of different flooding regime to the competition of MR219 and MR269 with weedy rice in this research did not significantly enhance the competitiveness of the cultivated rice. The harvest index and above ground biomass in both cultivated rice were significantly reduced by the competition of weedy rice in both nitrogen and water treatment. However, MR269 appeared to perform better in terms of tolerance to weedy rice competition for yield. Added N of 100 kg/ha can be said to enhance its performance. The result of this work showed that despite the cultivated rice competitive ability against the weedy rice biotypes, the weedy rice is agronomically and physiologically more vigorous, and weedy rice free condition would be essential for optimum rice yield.